The flow-performance relationship around the world - Ferreira, Miguel A.; Keswani, Aneel; Miguel, Antonio F.; Ramos, Sofia B. (Journal of Banking & Finance, 2012)
We use a new dataset to study how mutual fund flows depend on past performance across 28 countries. We show that there are marked differences in the flow-performance relationship across countries, suggesting that US findings concerning its shape do not apply universally. We find that mutual fund investors sell losers more and buy winners less in more developed countries. This is because investors in more developed countries are more sophisticated and face lower costs of participating in the mutual fund industry. Higher country-level convexity is positively associated with higher levels of risk taking by fund managers.